A Statistical Study between Beam and Layered Soil Using a Two-Parameter Elastic Foundation: Investigating the Influence of Soil Properties on Beam Interface Spectrum (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The thesis provides a finite element model of a beam that rests on a layered soil with two parameters. The conduct of the soil and the beam are supposed to be linear and uniform. The shear strain of the beam portion and the base of the soil are analysed together by the pressure energy expressions. This method elaborates and integrates the steadiness matrix of each factor in the study of the finite element. To demonstrate the appropriate method and the capability of the numerical programme designed for this purpose, different examples are developed first. Secondly, the research is expanded to explore how soil properties affect the spectrum of the interface and the beam responses. Third, a parametric analysis is carried out to illustrate the impact on interface interface spectrum of the location of springs, the soil characteristics, the depth of the soil base and the ballast sheet. Furthermore, shear deformations demonstrate the important effect on the beam, the configuration and the action of the interface. The findings achieved reveal relevant results for the interface spectrum and the beam answers.The thesis provides a finite element model of a beam that rests on a layered soil with two parameters. The behaviour, continuous, homogeneous isotropic, of the soil spectrum and the beam. The shear strain of the beam portion and the base of the soil are analysed together by the pressure energy expressions. This method elaborates and integrates the steadiness matrix of each factor in the study of the finite element. To demonstrate the appropriate method and the capability of the numerical programme designed for this purpose, different examples are developed first. Secondly, the research is expanded to explore how soil properties affect the spectrum of the interface and the beam responses. Third, a parametric analysis is carried out to illustrate the impact on interface interface spectrum of the location of springs, the soil characteristics, the depth of the soil base and the ballast sheet. Furthermore, shear deformations demonstrate the important effect on the beam, the configuration and the action of the interface. The findings achieved reveal relevant results for the interface spectrum and the beam answers.